Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1128/jvi.01552-07
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus K-Cyclin Interacts with Cdk9 and Stimulates Cdk9-Mediated Phosphorylation of p53 Tumor Suppressor

Abstract: K-cyclin, encoded by Kaposi's sarcoma-associated herpesvirus, has previously been demonstrated to activate cyclin-dependent kinase 6 (Cdk6) to induce the phosphorylation of various cell cycle regulators. In this study, we identified Cdk9 as a new K-cyclin-associated Cdk and showed that K-cyclin interacted with Cdk9 through its basic domain. We hypothesized that K-cyclin served as a regulatory subunit for the activity of Cdk9. Recent reports show that Cdk9 phosphorylates tumor suppressor p53, and we found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 78 publications
0
32
0
Order By: Relevance
“…The luciferase (Luc) reporter vectors p21-Luc and p2-mdm2-Luc, as well as the wild-type and mutant 14-3-3 luciferase reporter genes (32), were kind gifts of Larry Donehower (Baylor College of Medicine), and the SMRT DAD mutant (DADm; Y470A) was obtained from Mitch Lazar (19). Wild-type p53 was obtained from Addgene (Cambridge, MA) and cloned into pGEX-4T, while pGEX-4T-p53(1-300) and pGEX-4T-p53(300-393) were kinds gifts of Mengtao Li (33). The expression vectors for deletions in the SMRT N terminus, namely, SMRT-NT⌬36-312, SMRT-NT⌬36-388, and SMRT-NT⌬36-480, were generated by overlap extension PCR following a standard protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The luciferase (Luc) reporter vectors p21-Luc and p2-mdm2-Luc, as well as the wild-type and mutant 14-3-3 luciferase reporter genes (32), were kind gifts of Larry Donehower (Baylor College of Medicine), and the SMRT DAD mutant (DADm; Y470A) was obtained from Mitch Lazar (19). Wild-type p53 was obtained from Addgene (Cambridge, MA) and cloned into pGEX-4T, while pGEX-4T-p53(1-300) and pGEX-4T-p53(300-393) were kinds gifts of Mengtao Li (33). The expression vectors for deletions in the SMRT N terminus, namely, SMRT-NT⌬36-312, SMRT-NT⌬36-388, and SMRT-NT⌬36-480, were generated by overlap extension PCR following a standard protocol.…”
Section: Methodsmentioning
confidence: 99%
“…This same group has also shown that the addition of cdk inhibitors at the start of infection alters the levels and localization of cdk9 and cdk7 (15). More recently, the Kaposi's sarcoma-associated herpesvirus K-cyclin protein has been shown to interact with cdk9 (6).…”
mentioning
confidence: 94%
“…5,6 vCyclin binds to several Cyclin-dependent kinases (CDK) including CDK2, CDK4, CDK6, and CDK9 in vitro. [5][6][7][8][9] However, only vCyclin interactions with CDK6 and CDK9 have been shown to be functional in cells so far. The vCyclin-CDK6 complex has a large range of substrates including pRb, Bcl-2, histone Kaposi sarcoma-associated herpesvirus (KSHV) is a tumor virus encoding several proto-oncogenes.…”
Section: Introductionmentioning
confidence: 99%
“…5,7,[9][10][11][12][13][14] In PEL cell lines, phosphorylation by the vCyclin-CDK6 complex leads to p21 inactivation as well as p27 inactivation, cytoplasmic sequestration, and degradation, resulting in accelerated G 1 /S phase transition. 11,15,16 Single gene overexpression also causes vCyclin-dependent p27 degradation.…”
Section: Introductionmentioning
confidence: 99%